Background characteristics of unmanned aircraft for agricultural purposes - Матійчик, М.П.; Михайлов, Г.М.; Юн, Г.М. (Proceedings of National Aviation University (archive), 2007)
On the basis of calculations and experimental researches weight balances of the UAV main parts and also operational characteristics on an example of entering the protective substance – trihogramma are found out